منهج الإمام مالك بن أنس في الرواية عن عكرمة مولى عبد الله بن عباس - سناقرية, محمد علي; مغراوي, محمود (جامعة الوادي - University of Eloued, 2021)
يعد الإمام مالك من أوائل أئمة الجرح والتعديل، الذين سلكوا منهج التحري والدقة فـي فحص وانتقاء الرجال، حتـى شهد له أئمة هذا الشأن بثقة الرواة الذين روى عنهم سواء في الموطأ أو خارجه؛ إلا أن القارئ لتراجم رجال الموطأ أحيانا يقف عند راوٍ ضعيف بسبب سوء حفظه، أو فحش غلطه، أو إنحراف رأيه، وقد يعظم الأمر حين تجد في رجـــال الموطأ من يُتهم بالكذب، كعكرمة مــولـــى عبد الله بن عباس، الذي اتهم بالكذب ورُمِـــــي ببدعة الخروج وغيرها، فهذا أحــــد الرواة الذين تُكُلِم فــــي عدالتهم. فاحتوت هذه الدراسة علـــى ترجمة موجزة للإمام مالك لمعرفة مكانته عند المحدثين، وترجمة مختصرة لعكرمة للكشف عن حاله من حيث العدالة والضبط، من خلال كلام أهل الجرح والتعديل، بعدها تطرقتنا إلى تبيين رواية المحدثين عن عكرمة عامة، ورواية مالك عنه خاصة، ثم ذكرنا منهج المحدثين ومالك في الرواية عنه، والاحتجاج بخبره، مع التدليل بأمثلة تطبيقية من رواية مالك عن عكرمة، ثم ختمنا الموضوع بأهم النتائج التــي توصلنا إليها. Imam Malik was considered one of the first imams of al-Jarrah and al-Ta'idil, who followed the method of investigation and accuracy in examining and selecting men, until the imams testified for this matter with the confidence of the narrators who narrated about them, whether in the muwatta or outside it. However, the reader of the biographies of the men of the Muwatta 'sometimes stands with a narrator who is weak because of his poor memorization, obscenity, error, or deviation in his opinion, and the matter may be magnified when you find in the men of the Muwatta who is accused of lying, and among the narrators who have been spoken in their justice is Ikrimah, the master of Abdullah bin Abbas, who He was accused of lying and throwing out heresy, etc., for this is one of the narrators who spoke about their justice. This study included a brief translation of Imam Malik to know his position among the hadiths, and a brief translation of Ikrimah to reveal his condition in terms of justice and discipline, through the words of the people of al-Jarrah and al-Ta`dil. And Malik in the narration on him, and the invocation of his experience, while demonstrating practical examples from Malik's narration on Ikrimah, then we concluded the topic with the most important results that we reached, along with some useful recommendations for students of the sciences of the Prophet’s Sunnah
مقال في مجلة الشهاب بجامعة الوادي
Keywords: ، الرواية، مالك بن أنس، عكرمة